Development Of Component Parts Of The Professional Competence Of The Future Specialist - Senior Lecturer R.A.Mavlonov; Trainee Teacher A.R.Mirzamakhmudov (Zien Journals, 2023)
The article covers the issues of development of the components of professional competence of the future specialist based on the researches of theorists involved in the implementation of the competent approach in higher education practice.
Keywords: intellectual competence; decision-making; knowledge